1987
DOI: 10.1136/jnnp.50.5.593
|View full text |Cite
|
Sign up to set email alerts
|

F-response frequency in motor neuron disease and cervical spondylosis.

Abstract: SUMMARY During a train of 200 stimuli, F-response frequency, frequency of identical responses, and F-response shape were studied in the ulnar nerve of 17 patients with motor neuron disease (MND) and 16 patients with cervical spondylosis (CS). In MND patients, F-response frequency varied between 5% and 96% with a median of 39% which was significantly lower than controls (p < 0 001), and showed a significant rank correlation with the M-response amplitude (r = 0-62, p < 0.004). Identical responses occurred more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 9 publications
5
24
0
Order By: Relevance
“…[24][25][26][27][28][29][30] The main reason for this is probably that the association of upper and lower motor neuron signs in ALS makes the interpretation of the ndings markedly more dif cult than in 'pure' syndromes.…”
Section: Discussionmentioning
confidence: 93%
“…[24][25][26][27][28][29][30] The main reason for this is probably that the association of upper and lower motor neuron signs in ALS makes the interpretation of the ndings markedly more dif cult than in 'pure' syndromes.…”
Section: Discussionmentioning
confidence: 93%
“…A correlation between F-response frequency and M-response amplitude has been reported in ALS, with reduced Fresponse frequency in weak muscles. 45 We found that the F-wave frequency was progressively reduced in weaker muscles (Tables 1 and 2), being lowest in MRC 2-1 muscles (39% with no F waves). We found that F-wave dispersion was increased in weaker muscles.…”
Section: Discussionmentioning
confidence: 93%
“…These include increased F-wave latencies 3,12,36,41 with normal F-wave frequency 41 and increased F-wave amplitudes, 3 and slowing of F-wave velocities with decreased F-wave frequency. 13 Decreased F-wave frequency has been related to the degree of muscle atrophy, and an increased number of repeating responses 45 has been reported. Muscle strength in ALS is probably mainly related to lower motor neuron function, 7,25,35 with upper motor neuron dysfunction being less important.…”
mentioning
confidence: 98%
“…Similar findings have been reported in patients with motor neuron disease, in whom F-response persistence correlated with CMAP amplitude. 11 It should be noted that if CMAP amplitudes were less than 500 mV, then F-response parameters were not included in the analyses. This was because we believe that the CMAP must be clearly present before commenting on the nature of the F-response abnormalities.…”
mentioning
confidence: 99%